2021
DOI: 10.1016/j.bonr.2021.101151
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of osteoporotic fractures in alkaptonuria by teriparatide stimulates bone formation and decreases fracture rate – A report of two cases

Abstract: Two cases of advanced alkaptonuria (AKU) with co-existing osteoporosis are described. Case 1 developed multiple non-vertebral fragility fractures, while Case 2 developed vertebral fragility fractures, both refractory to bisphosphonates. Difficulties in diagnosing osteoporosis in AKU complicated by extensive calcifying and ossifying spondylosis are discussed. Both patients continued to fracture despite nitisinone therapy for metabolic control of AKU, as well as bisphosphonate antiresorptive therapy for osteopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…After 5 years of treatment with bisphosphonates, our patient was treated with teriparatide. More recently, Ranganath et al in 2021 have also demonstrated the effectiveness of teriparatide in 2 AKU patients 6 . Thus, our patient represents the third AKU patient with bisphosphonate‐resistant osteoporosis who was treated successfully with teriparatide.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…After 5 years of treatment with bisphosphonates, our patient was treated with teriparatide. More recently, Ranganath et al in 2021 have also demonstrated the effectiveness of teriparatide in 2 AKU patients 6 . Thus, our patient represents the third AKU patient with bisphosphonate‐resistant osteoporosis who was treated successfully with teriparatide.…”
Section: Discussionsupporting
confidence: 52%
“…More recently, Ranganath et al in 2021 have also demonstrated the effectiveness of teriparatide in 2 AKU patients. 6 Thus, our patient represents the third AKU patient with bisphosphonate‐resistant osteoporosis who was treated successfully with teriparatide. The anabolic actions of PTH occur because of its direct effects on cells of the osteoblast lineage and indirect effects through the induction of IGF‐I (insulin‐like growth factor‐1) and the suppression of sclerostin with the consequent enhancement of Wnt signaling and by suppressing Notch signaling.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…There are a good number of publications on alkaptonuria presenting with arthritis but there are only a handful of case reports in the context of fractures. Ranganath et al [ 5 ] described two cases of advanced alkaptonuria with coexisting osteoporosis. One patient developed multiple non-vertebral fragility fractures and the other patient developed vertebral fragility fractures while on nitisinone therapy and bisphosphonates therapy.…”
Section: Discussionmentioning
confidence: 99%